Comparison of Necrotizing Enterocolitis in Pre-mature Infants vs. Term-Born Infants With Congenital Heart Disease - Frid, Gabriela; Reppucci, Marina; Lum, Tony; Paul, Megan; Seiden, Howard; Coakley, Brian A. (Frontiers in Pediatrics, 2021)
PURPOSE: Necrotizing enterocolitis (NEC) is a serious illness that occurs among premature in-fants and term-born infants with congenital heart disease (CHD). Prior studies have suggested these two groups may experience different disease entities. We sought to evaluate if there are differences in disease characteristics between these two populations. MATERIALS AND METHODS: A retrospective chart review of infants treated for Bells stage 2-3 NEC from 2011-2020 was performed. Demographic information, CHD diagnoses and clinical data were recorded. Prior to data analysis, patients were divided into two groups: term-born patients with CHD (TC) and premature patients without CHD (PT). RESULTS: 99 patients were analyzed--23 TC patients and 76 PT patients. Platelet counts (222.7 ± 176.1 vs. 310.2 ± 174.5 cells/uL, P = 0.03) and C-reactive protein (CRP) levels (53.6 ± 81.7 vs. 117.6 ± 90.4 mg/L, P < 0.001) were significantly higher among the PT group. In addition, PT patients were more likely to develop pneumatosis (30.4% vs. 68.4%, P = 0.002) than TC patients. NEC-specific mortality was similar between both groups of patients. CONCLUSIONS: When compared to TC patients, PT patients had higher CRP levels, higher platelet counts and more commonly developed pneumatosis. These factors may point towards a difference in disease pathophysiology regarding NEC development in premature patients versus term-born patients with CHD.